2020
DOI: 10.33859/dksm.v10i1.437
|View full text |Cite
|
Sign up to set email alerts
|

Komunitas Masyarakat Dan Perawatan Kesehatan Dalam Peningkatan Kualitas Hidup

Abstract: Latar belakang: Seiring dengan perkembangan jaman, dalam beberapa tahun terakhir ini banyak perhatian yang difokuskan pada eksplorasi dampak penyakit fisik dan mental pada kualitas hidup seseorang baik secara individu maupun masyarakat secara keseluruhan. Sifat subyektif dari 'kualitas hidup' individu, merupakan konsep yang dinamis untuk diukur dan didefinisikan, tetapi bahwa secara umum dapat dipandang sebagai konsep multidimensi yang menekankan pada persepsi diri dari keadaan pikiran seseorang saat iniTujuan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Therefore it is important for individual abilities to be maximized as an indicator of the ability to adapt to their environment. Quality of life will produce positive and negative impacts if a person performs his life functions only for satisfaction in carrying on life (Hermino, 2020). So it can be concluded that quality of life is a level measured by health status and physical function in carrying out daily activities for the full or maximum welfare of his life.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it is important for individual abilities to be maximized as an indicator of the ability to adapt to their environment. Quality of life will produce positive and negative impacts if a person performs his life functions only for satisfaction in carrying on life (Hermino, 2020). So it can be concluded that quality of life is a level measured by health status and physical function in carrying out daily activities for the full or maximum welfare of his life.…”
Section: Discussionmentioning
confidence: 99%
“…Pusat Pengendalian dan Pencegahan Penyakit (CDC) mendefinisikan kualitas hidup sebagai persepsi individu tentang kondisi kesehatan fisik dan mental serta hubungannya dengan risiko dan kondisi kesehatan, status fungsional, dukungan sosial, dan status sosial ekonomi (Romadhoni et al, 2020). Kualitas hidup juga dapat diartikan sebagai konsep multidimensi dinamis yang dirancang untuk menentukan dampak psikologis dari suatu penyakit, meliputi aspek kesejahteraan ekonomi, karakteristik masyarakat dan lingkungan, dan keadaan kesehatan (Hermino, 2019;Ekasari et al, 2019).…”
Section: Pendahuluanunclassified
“…Health is defined as a state of physical, mental and social well-being not just the absence of disease or weakness (Hermino, 2019;Sari & Manungkalit, 2019). Health, in its holistic philosophy, is very different from the acute care setting.…”
Section: The Meaning Of Healthmentioning
confidence: 99%
“…This process involves people, families and communities. Regarding this, health is reflected as the experience of people living in good health, living in a style of good health with energy to be developed very well (Hermino, 2019;Kozier, 1995).…”
Section: Environmental Model For Healthmentioning
confidence: 99%
See 1 more Smart Citation